Transient and seasonal performance evaluation of a novel flexible heat pump for solar cooling. (1st November 2020) - Wu, Wei; Leung, Michael
Highlights: A novel flexible heat pump is proposed to accommodate different solar resources. Thermodynamic/transient/seasonal features of the solar cooling system is studied. Seasonal COP reaches 7.2 and 8.9 for flat-plate and evacuated-tube collectors. Energy saving reaches 21.2% and 31.8% for flat-plate and evacuated-tube collectors. Evacuated-tube better than flat-plate; collector area affects more than tank volume. Abstract: Solar cooling plays an important role in low-carbon societies. The existing solar cooling systems commonly suffer from low energy efficiency or low applicability. To solve this problem, a novel solar-powered flexible HEHP (hybrid-energy heat pump) is proposed. Firstly, thermodynamic and TRNSYS models are established with verified accuracies. Using the models, the steady-state HEHP performance is investigated under various operating modes and working parameters. In addition, transient characterization shows that the solar-based modes operate longer than the non-solar mode with RAHP (absorption ratio) ranging in 0.3–1.0. With enhanced cooling capacities, the HEHP mode generally operates at high cooling loads. The seasonal performance is compared between FPC (flat plate collector) and ETC (evacuated tube collector), concluding that the ETC-based HEHP performs much better than the FPC-based HEHP. The collector area greatly affects the system performance; as the collector area increases from 0 to 300 m 2, the load fraction of the solar-based modes significantly increases from 0 to 0.69 for FPC and from 0 to 0.93 for ETC, the seasonal COP (coefficient of performance) respectively rises from 5.5 to 7.2 and from 5.5 to 8.9, while the energy saving ratio (ESR) respectively reaches 21.2% and 31.8%. As for the tank volume, it has a much smaller influence; with the specific tank volume increasing from 0.01 to 0.06 m 3 /m 2, the ESR slightly varies from 15.1% to 17.3% for FPC and from 25.1% to 28.4% for ETC. This study aims to facilitate the development, design and operation of the solar HEHP cooling system.